Analisis Tingkat Keuntungan, Keunggulan Kompetitif, Keunggulan Komparatif, dan Dampak Kebijakan Impor Pada Usaha Peternakan Sapi Potong di Provinsi Jawa Barat - Dwi Yuzaria; Dadi Suryadi (Agricultural Faculty, 2011)
The analysis of profitability, comparative advantage, competitive advantage and import policy impact on beef cattle fattening in west javaABSTRACT. The beef cattle fattening in Indonesia is financially and economically beneficial, even though the production process is in an economical condition with various trading policies with others countries. Those including the policies of import tarrif and quota on input that are aimed to have a more expensive price of import input, hence giving the chance for domestic input to compete. These will be an advantage for domestic feedloter, however the result of governmental policy are often far from expectation. Research conducted in West Java. This research used the survey method, with multistage random sampling and analyzed by using the Policy Analysis Matrix model to measure the efficiency of the business performance of beef cattle fattening. Result of the research shows that beef cattle fattening reached financial and economical benefits. Feedloters of local and imported cows in west Java has competitive advantage, local cows is more competitive than imported cows. Meanwhile efficiency indicator shows that feedloters of imported cows has more comparative advantage compared to the feedloters of local cow.